Islamic Banking and Economic Development: Insights from Southeast Asia and the Middle East - Hajar, Andi (Yayasan Sinergi Kawula Muda, 2024)
This study presents a comprehensive narrative review of contemporary developments, challenges, and prospects in Islamic finance and banking, particularly within developing economies. The research aims to evaluate the sector's effectiveness in promoting financial inclusion, ethical investment, and sustainable development. Using a structured search methodology across Scopus, Google Scholar, and DOAJ, relevant literature was selected based on thematic keywords and inclusion criteria focusing on empirical studies and policy-oriented analysis. Key findings indicate that Islamic financial literacy strongly influences investment behavior among Muslim investors by reducing perceived risk and aligning investment choices with ethical values. Shariah governance, particularly the role of Supervisory Boards, is pivotal but faces implementation disparities across countries. Product innovation in markets like Malaysia and Indonesia exemplifies the sector's responsiveness to financial modernization while adhering to Shariah principles. Moreover, Islamic finance aligns with sustainable development goals through instruments such as green sukuk and zakat, offering ethical alternatives for environmental and social financing. Systemic challenges persist, including inconsistent regulatory environments, limited public understanding, and fragmented interpretations of Shariah law. To address these, the study recommends enhancing regulatory alignment, promoting public education, and strengthening institutional collaboration. These findings underscore the transformative potential of Islamic finance in achieving inclusive and sustainable economic outcomes.